The Performance Evaluation of State Grassland Ecological Compensation and Rewards—A Case Study in Yili, Xinjiang, China - Li, Dan; Han, Fengqin (International Journal of Economics, Business and Management Studies, 2021)
Since 2011, the State Grassland Ecological Compensation and Rewards(GECR) had implemented in 13 provinces (regions) in China. This policy controlled livestock carrying capacity on pasture and provided subsidies to pastoralists, aimed at reducing livestock number on grassland, increasing income of pastoralist households, and restoring degraded grassland ecosystem. Taking Nileke County of Xinjiang, China as a case study, this research evaluated the ecological, economic and social performance of GECR in agro-pastoral area. Using annual series data during 2006-2010 and 2011-2015, the change of grassland ecological condition, household living standard and labor population was compared between the two periods, and the influence of GECR were validated and detailed with semi-structured household interviews. The results showed that after 2011, livestock number in pastoral area decreased. In contract, the livestock in agricultural area showed large growth. Farmers’ livestock use pasture through grazing transaction, which means farmers paid herders to graze their livestock on the herder’s pasture. Widespread transactions between farmers and herders led to overgrazing on pasture and grassland degradation. GECR also had no significant contribution on improving household income and encouraging livelihood transition. The policy had no significant benefits in ecology, economy and society in case area. Based on the findings, we put forwards suggestions from three aspects: improving the design of the GECR policy, establishing performance evaluation system, strengthening the supervision and punishment of grassland overgrazing and improving local human capital quality .